Digital Security Literacy of Bank and Fintech Customers: The Role of Educational Communication in Preventing Social Engineering - Furqon, Moh. Ajuk Alif (GoAcademica Research & Publishing, 2025)
The transformation of digital financial services has created both significant opportunities and challenges in maintaining customer security from various forms of cyber threats. The increasing complexity of financial technology has encouraged financial institutions to develop more effective and adaptive communication strategies to foster customer awareness and protective behavior. However, there remains a gap between the intensity of communication and actual changes in customer behavior in the face of digital risks. This study aims to analyze the effectiveness of communication in shaping customer security behavior, particularly in the context of digital financial services. The method used was a qualitative approach, collecting data from relevant previous studies and institutional documentation. The data obtained were analyzed thematically and interpretively to uncover patterns of relationships between communication strategies and changes in customer behavior. The results show that the intensity of educational communication is strongly correlated with increased customer awareness of digital security risks. Customer response is strongly influenced by the appropriateness of the type of message and the media used to convey the information. Furthermore, a more participatory and down-to-earth communication approach is needed so that digital protection messages can be truly internalized and reflected in customers' daily behavior.